Market surveillance: analysis of perfuming products for presence of allergens and prohibited substances - Ševčík, Václav; Andraščíková, Mária; Vavrouš, Adam; Moulisová, Alena; Vrbík, Karel; Bendová, Hana; Jírová, Dagmar; Kejlová, Kristina; Hložek, Tomáš (Chemical papers, 2022)
The market surveillance study was based on chemical analysis of 166 commercially available perfuming products in order to identify the presence of 24 regulated allergens and 21 prohibited substances. For this purpose, several GC methods were tested. The analytical approach for determination of 24 regulated allergens was based on GC–MS and GC–MS/MS analysis. Analyses were performed on two different GC columns to avoid potentially overestimated results due to matrix component co-elutions. Allergens determined by the chemical analyses were compared with the allergens declared on the product label to verify whether these products comply with the requirements of the Regulation No 1223/2009 of the European Parliament and of the Council. A specific proportion of the tested cosmetic products (43%) was found as non-compliant either due to a missing list of ingredients or due to the presence of undeclared allergens that were found to be present in the product above limits (0.001%) for required labelling. The GC–MS/MS analysis of 21 prohibited substances did not reveal any of the prohibited compounds in a concentration above LOQ except safrole, which was found in 12 out of 166 tested samples. The concentration of safrole did not exceed the concentration limit permitted by legislation for the presence from natural sources in any of these samples.